Recent preclinical and clinical advances in oligonucleotide conjugates. (3rd June 2018) - Craig, Kevin; Abrams, Marc; Amiji, Mansoor
ABSTRACT: Introduction: Oligonucleotide therapeutics have the potential to change the way disease is treated due to their ability to modulate gene expression of any therapeutic target in a highly specific and potent manner. Unfortunately, this drug class is plagued with inherently poor pharmacological characteristics, which need to be overcome. The development of a chemical modification library for oligonucleotides has addressed many of the initial challenges, but delivery of these payloads across plasma membranes remains difficult. The latest technological advances in oligonucleotide therapeutics utilizes direct conjugation to targeting ligands, which has improved bioavailability and target tissue exposure many-fold. The success of this approach has resulted in numerous clinical programs over the past 5 years. Areas Covered: We review the literature on oligonucleotide conjugate strategies which have proven effective preclinically and clinically. We summarize the chemical modifications which allow parenteral administration as well as evaluate the efficacy of a multitude of conjugate approaches including lipids, peptides, carbohydrates, and antibodies. Expert Opinion: The success of future conjugate strategies will likely rely on the effective combination of characteristics from earlier technologies. High-affinity ligand-receptor interactions can be critical to achieving meaningful accumulation in target tissues, but pharmacokinetic modulators which increase the circulating half-life may also be necessary. Synthesis of these approaches has the potential to bring the next breakthrough in oligonucleotide therapeutics.